The Index of Asia-Pacific Regional Integration Effort - Victor Yifan Ye; Mia Mikic (East Asian Economic Review (EAER), 2016)
The Asia-Pacific region is not typically seen as one geographic or socio-economic space. Yet, 58 regional economies occupying the space of 28 million square kilometers from Turkey in the West, Russian Federation in the North, French Polynesia in the East and New Zealand in the South belong to the Economic and Social Commission of Asia and the Pacific (ESCAP). This commission provides a forum for member states that "promotes regional cooperation and collective action, assisting countries in building and sustaining shared economic growth and social equity". In 2013, ESCAP's members adopted the Bangkok Declaration to enhance efforts towards deeper regional economic integration. Yet this document neither proposes a concrete modality or modalities of achieving deeper integration, nor provides a sense of distance of individual countries to a "perceived" integrated Asia-Pacific.This paper aims to comprehensively quantify recent integration efforts of economies in the Asia-Pacific region. We provide an "index of integration effort" based on twelve metrics that measure the relative distance of a given economy to the region as an economic entity. Generally, we find that while the region has trended towards becoming integrated in general, both the level of integration and integration effort are inconsistent among Asia-Pacific economies. We discuss potential applications and extensions of the index in developing our perspective of the region's economic and social dynamics.
Keywords: O53; Y10; 330; Regional Integration Effort; Asia-Pacific; Index of Integration Effort; Social and Economic Integration; ESCAP; Trade Agreements; Investment Agreements